Avaliação da qualidade das águas de açudes no município de Angicos-RN: estudo de caso - Santos, André Luiz Barbalho dos (Universidade Federal Rural do Semi-Árido, 2019)
The objective of this study was to evaluate the physicochemical quality of the waters of the three urban reservoirs of the city of Angicos-RN, for irrigation purposes, aiming to define recommendations for improving the quality of their waters for the dry and flood periods. Thus, the analyzed parameters valued both soil and plant quality, some of them were electrical conductivity (EC), chloride (Cl−), sodium (Na +), calcium (Ca2 +) and magnesium (Mg2 +); in addition to the concentration of heavy metals, such as copper (Cu), iron (Fe) and lead (Pb). In most of the analyzes performed, Caraubinhas and Novo Angicos reservoirs showed satisfactory results regarding the standards used as reference, in contrast to José Teodoro reservoir, which presented higher values than allowed in several analyzes, such as chloride, copper and lead. The chloride presented concentrations within the parameters established by the standard in the Caraubinhas and Novo Angicos reservoirs, while the José Teodoro reservoir had higher concentrations, with results ranging from 6.4 to 6.8 mmolc / L. Lead was one of the heavy metals that recorded concentrations only for José Teodoro reservoir, and these showed higher values than established by legislation (0.01 mg / L). Therefore, it was evidenced that each one of the reservoirs was classified with a quality level for irrigation use, with Caraubinhas reservoir presenting good conditions, Novo Angicos reservoir evidencing an average quality and José Teodoro reservoir was classified as irregular.
Artigo
Keywords: Irrigação; Metais pesados; Classificação; Cloreto; Sódio; Irrigation; Heavy metals; Ranking; Chloride; Sodium; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA